(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the phenomena of semantic narrowing and semantic broadening observed in Arabic loanwords in the modern Uzbek language. It examines the role of Arabic borrowings in the lexical system of Uzbek, their historical formation, and the processes of semantic development on a scientific basis. The study also explains the linguistic and extralinguistic factors influencing changes in word meaning, including social, cultural, historical, and stylistic aspects. The findings contribute to identifying the semantic features of Arabic loanwords and to a deeper understanding of the lexical richness of the Uzbek language.